2020
DOI: 10.28991/cej-2020-sp(emce)-07
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Strengthening of Reinforced Concrete Beams with Externally-Bonded Fibre Reinforced Polymer: An Energy Absorption Evaluation

Abstract: The impacts of numerous important factors on the Energy Absorption (EA) of torsional Reinforced Concrete (RC) beams strengthened with external FRP is the main purpose and innovation of the current research. A total of 81 datasets were collected from previous studies, focused on the investigation of EA behaviour. The impact of nine different parameters on the Torsional EA of RC-beams was examined and evaluated, namely the concrete compressive strength (f’c), steel yield strength (fy), FRP thickness (tFRP), widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…During an extensive parametric study, several important elemental effects on the energy absorption of torsional RC beams reinforced with external FRP were investigated [21]. The findings demonstrate that the concrete compressive strength, FRP thickness, and vertical steel ratio were the most crucial factors influencing the RC beams torsional energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…During an extensive parametric study, several important elemental effects on the energy absorption of torsional RC beams reinforced with external FRP were investigated [21]. The findings demonstrate that the concrete compressive strength, FRP thickness, and vertical steel ratio were the most crucial factors influencing the RC beams torsional energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that machine learning techniques outperform traditional methods in terms of their performance. Conventional regression methods have a key drawback in that they require a suitable initial model parameter set [31]. In addition, conventional methods may end up in multiple local minima, which is a problem.…”
Section: Pso Algorithmmentioning
confidence: 99%
“…It was found that the mesoscale numerical model produced findings that were closer to the experimental data, and that mesoscale modeling of reinforced concrete is most convenient when the maximum aggregate size is reduced. Hason et al investigated the effects of numerous critical parameters on the energy absorption (EA) of torsional RC beams reinforced with external FRP [31]. Whereas, (81) gathered datasets for investigating (28) factors were studied and evaluated including the concrete compressive strength through using response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 99%
“…Structures containing thin-walled elements may be damaged by other types of loading, e.g., cyclic loading-the consequences of which may be disastrous for the load-bearing capacity of the structure. The effects on load-bearing capacity and energy absorption in these cases are described in the following papers [34][35][36][37]. Nowadays, the finite element method is widely used in analysis; with the help of its advanced solvers, it is possible to calculate complex models using fracture of materials or their deformation during dynamic loading modes [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%